Clinical practice guidelines on the use of aspirin in pregnancy: Systematic review. (March 2023) - Di Girolamo, Raffaella; Alameddine, Sara; Khalil, Asma; Santilli, Francesca; Rizzo, Giuseppe; Maruotti, Giuseppe Maria; Liberati, Marco; D'Antonio, Francesco
Abstract: Background: Placental related disorders, including preeclampsia and fetal growth restriction (FGR) are among the main determinants of adverse maternal and perinatal outcomes in both singleton and twin pregnancies. In view of its relevance, aspirin administration is commonly recommended to women at high risk for preeclampsia or FGR by the various national and international guidelines. Objectives: To establish the clinical heterogeneity among the clinical practice guidelines (CPGs) on aspirin use in pregnancy and to investigate the quality of these CPGs. Methods: We performed a systematic review of Clinical practice guidelines on main databases searching for all peer-reviewed guidelines into the literature, analyzing the following aspects related to use of aspirin in pregnancy: indications for aspirin administration, dosage, starting of therapy, ending of therapy, safety and side effects. The assessment of risk of bias and quality assessment of the included CPGs were performed using "The Appraisal of Guidelines for REsearch and Evaluation (AGREE II)" tool. Results: 16 CPGs were included. There was an overall general agreement among the published CPGs as regards to the indication for aspirin intake in pregnancy, with prior preeclampsia, chronic hypertension, autoimmune disease, and diabetes mellitus type 1 or 2 recognized as solitary major risk factors for Aspirin administration in 93.7% (15/16) of CPGs. There was heterogeneity in the recommendations provided by the different CPGs as regards the gestational age at which aspirin should be commenced. Conclusion: There is general agreement in the reported indications for aspirin intake in pregnancy, with prior preeclampsia and maternal medical co-morbidity associated with increased risk of preeclampsia being the major indications for aspirin intake. Conversely, there was heterogeneity in the recommended dose, gestational age at initiation and discontinuation of therapy among the different CPGs.